Promosi Kesehatan Manajemen Kebersihan Menstruasi pada Remaja Putri di MI Attarbiyatul Islamiyah, Kudus, Jawa Tengah: Health Promotion, Menstrual Hygiene Management in young Women at MI Attarbiyatul Islamiyah, Kudus, Central Java - Adyani, Kartika; Realita, Friska (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Menarche, or the first menstruation, is a primary physiological change marking the onset of puberty in adolescent girls, characterized by vaginal bleeding. Proper menstrual hygiene management is essential to maintain reproductive health. Adolescents' knowledge and attitudes play a significant role in shaping personal hygiene behaviors during menstruation. However, most students at MI Attarbiyatul Islamiyah have not received direct education regarding menstrual hygiene management. This community service activity aimed to improve students' knowledge and skills related to menstrual preparation and appropriate hygiene practices. The intervention involved educational video presentations, practical demonstrations, interactive games, and question-and-answer sessions. The participants were 43 fifth-grade female students at MI Attarbiyatul Islamiyah. The results indicated an increase in students' knowledge and skills, including proper sanitary pad usage, sanitary pad disposal management, pain relief using warm compresses, and correct genital cleansing techniques.